A world catalogue of Xyleutes Hübner, 1820 (Lepidoptera: Cossidae: Zeuzerinae) with description of a new species from the Western Ghats of India - Yakovlev, Roman V.; Sankararaman, Hariharakrishnan; Balaji, Rajasekaran Krishna; Balakrishnan, Valappil (Zootaxa, 2021)
A new species of carpenter moth Xyleutes ramamurthyi Yakovlev & Sankararaman, sp. nov. (Lepidoptera, Cossidae, Zeuzerinae) is described as new to science from the Western Ghats of south India. The identification key and species catalog of the genus is provided. In this study, we illustrated with images of all the species of the genus and morphological structures of the new species. The photos of biotopes and the map of new species distribution are provided.